An Advanced Frequency Estimation Algorithm Based on Analytic Compensation of Effects of Dominant Harmonic in Power Systems - Kyou Jung Son (IEEE, 2021)
This paper proposes an advanced frequency estimation algorithm, where the interference effect of harmonic is effectively compensated by proposing and using a new ‘harmonics interference decomposition model’. In the decomposition model, the interference effect of harmonic is represented as the sum of the two separated components, i.e., a deviation bias and an oscillatory disturbance, where the deviation bias is modeled to include only the uncoupled amplitude parameter terms and the oscillatory disturbance is modeled to exclusively include all the phase parameter coupled terms in representing a power spectral peak location. The separation and the independent compensation of the two interfering parameters significantly reduce the nonlinearity associated difficulties in deriving analytic compensation equations. Frequency estimation performance of the proposed algorithm is verified through computer simulations with diverse patterns of power system signals. The proposed algorithm’s excellent estimation accuracy and rapid convergence performance are confirmed by comparing the simulation results with those of other representative algorithms.